Hydroxypropyl methylcellulose-based films embedded with garlic oil-loaded chitosan microparticles as a potential oral mucosal drug delivery system / Nur Jemaima Muhammad Ridzwan Ramond and Nor Khaizan Anuar - Muhammad Ridzwan Ramond, Nur Jemaima; Anuar, Nor Khaizan (Faculty of Pharmacy, 2021)
In the present study, hydroxypropyl methylcellulose (HPMC)-based films embedded with garlic oil-loaded chitosan microparticles were characterized and evaluated for their suitability as a potential oral mucosal drug delivery system concerning bacterial infections. Chitosan was used to encapsulate garlic oil and form microparticles using different weight ratios by ionic gelation technique. The microparticles were then incorporated into HPMC solution and films were fabricated using the film casting technique. A blank film without microparticles was also prepared. The microparticles were examined for their particle size, uniformity, shape, zeta potential and antimicrobial activities. The results suggest that the microparticles exhibit a spherical shape, are electrically unstable and tend to agglomerate due to having low zeta potential (-7.06 to -1.24 mV). Nevertheless, they showed antimicrobial activities against both Escherichia coli and Staphylococcus aureus. Additionally, the films were characterized by weight, thickness, wettability and antimicrobial activities. All films produced were generally light (0.20 to 0.25 g), thin (0.02 to 0.12 mm) and had good wettability based on their low contact angles (below 90°). In comparison to the microparticles, the films exhibited antimicrobial activity against S. aureus whereas no zone of inhibition was observed when the films were tested against E. coli. HPMC-based films embedded with encapsulated garlic oil have the potential to act as a new drug treatment to treat oral mucosal bacterial infections. Additional studies should be performed to evaluate the effectiveness of this treatment, such as extensive physicochemical characterization, mucoadhesion studies and evaluation of drug release and drug permeation across the oral mucosa.